Medina de Constantine Restitution du « souk el-kbir » - HARKATI, Meriem; Mr. ALIKHODJA, Nadhir (Encadreur); Mme BOUSNINA, Mounia (Co-Encadreur) (Université Ferhat Abbas Sétif 1. Institut d'architecture et sciences de la terre. Département d'architecture ., 2015)
This work shows an intervention in a protected area: the medina of Constantine, classified as a national heritage since 1990, is a traditional tissue sector. The process of intervention begins with a global analysis on the medina, for the reason of understanding the logics and principles of this tissue, the second step, is a detail analysis, of a specific sector in the medina "souk and-Tojjar" for the reason for the mastery. Is the diagnostic phase which guides the proposal actions, detailed actions are "the restitution of the Souk El-Kabir", " the reorganization of Rahbat es-souf ", "embellishment the facades of Rahbat es-souf ".
يقدم هذا العمل, عملية تدخل داخل منطقة محمية التي هي المدينة العتيقة لقسنطينة, حيث صنفت منذ سنة 0991 كتراث وطني. تعتبر هذه الاخيرة كمنطقة ذات نسيج عمراني تقليدي. تمر هذه العملية بعدة مراحل: أولها, قراءة وتحليل للمدينة بصفة عامة لغاية فهم المنطق و المبادئ الذي يرتكز عليها هذا النسيج العمراني, ثم مرحلة القراءة التفصيلية التي تشمل منطقة معينة و هي "سوق التجار". تعتبر هذه المرحلة كمرحلة تشخيص التي توجه من خلال نتائجها مخطط التدخل , التدخلات المقترحة هي: "عملية استرجاع للسوق الكبير" ,"إعادة تنظيم رحبة الصوف" ,"إعادة تجميل واجهات رحبة الصوف"
Keywords: Médina; Souk; Rahbat; Restitution; Valeur mémorielle; Rahbat es-Souf